Le ricadute dell’emergenza sanitaria sulle procedure di fecondazione assistita (TEST BioLaw Journal - Rivista di BioDiritto, 2020)
The paper analyzes the impact of CoViD-19 emergency on medically assisted procreation procedures. The aim is to draw from this specific case some ideas for a wider reflection on the issue of assisted fertilization and on the constitutional rights involved.
Keywords: CoViD-19; pandemic emergency; medically assisted procreation; constitutional rights and freedoms; health